USE OF FIXED COMBINATIONS OF RAMIPRIL AND HYDROCHLOROTHIAZIDE IN PATIENTS WITH ARTERIAL HYPERTENSION AND HIGH OR VERY HIGH CARDIOVASCULAR RISK (OPTIMIST 2 STUDY): RESULTS OF THE NONCOMPARATIVE STUDY - I. A. Velizhanina; L. I. Gapon; E. S. Velizhanina; A. V. Rudakov; T. S. Zhupanova (Рациональная фармакотерапия в кардиологии, 2016)
Aim. To evaluate efficacy and safety of treatment with fixed combination of ramipril and hydrochlorothiazide in patients with arterial hypertension (HT) 2-3 degree and high or very high cardiovascular risk in clinical practice. Material and methods. Patients with HT 2-3 degree and high or very high cardiovascular risk who had not reached target blood pressure (BP) levels with previous therapy (n=427) were included in open-label non-comparative multicenter phase IV study. Patients were treated with fixed combination of ramipril and hydrochlorothiazide during 8 weeks. The drug dose was increased and/or amlodipine was added in case of insufficient antihypertensive effect. Achievement of the target BP level (<130/80 mmHg) and therapy safety were assessed. Results. 420 patients (98.4%) completed the study. After 8 weeks 273 (65%) patients had a two-component therapy (fixed combination of ramipril and hydrochlorothiazide), 147 (35%) patients — triple therapy (ramipril, hydrochlorothiazide and amlodipine). The target BP level was achieved in 408 (97.14%) patients and it was not reached in 12 (2.86%) patients. 7 patients were dropped out from the study: 4 — because of adverse events (dry cough), 3 — due to violation of study protocol. Both patients and doctors considered fixed ramipril and hydrochlorothiazide combination as effective and well tolerable one.  Conclusion. Ramipril and hydrochlorothiazide fixed combination provides an achievement of the target BP level in the most of HT patients.